Epilepsy and sleep: current diagnostic and treatment approaches - N. I. Shova; A. K. Bolshakova; V. A. Mikhailov (Эпилепсия и пароксизмальные состояния)
Background. Multiple complicated interactions exist between sleep and epilepsy – sleep activating effect on emerging epileptic seizures, altered sleep pattern due to epileptic activity, antiepileptic drugs impact on sleep pattern in epilepsy patients, as well as comorbidity of sleep disorders and epilepsy.Objective: exploring a literature-based relationship between sleep and epileptic activity, as well as approaches to the diagnosis and treatment of sleep disorders in epilepsy.Material and methods. Current literature review examined the data of presented analysis assessing a relationship between epilepsy and sleep. Publications were searched in the electronic databases PubMed/MEDLINE and eLibrary using key words and phrases: “epilepsy”, “sleep”, “antiepileptic drugs”, “sleep disorders”, “insomnia”, “obstructive sleep apnea syndrome”, “restless legs syndrome”, “depression”, “anxiety”, “non-psychotic mental disorders” in Russian and English.Results. A literature review revealed complex relationships between epilepsy and sleep disorders. Epileptic activity, especially at night, can fragment sleep, reducing its restorative potential and provoking higher seizure incidence and severity. It was also shown that different antiepileptic drugs (AEDs) have ambiguous effects on sleep patterns: sedative AEDs may improve sleep, but may cause excessive daytime sleepiness if dosage and timing of administration are inappropriate. Challenges in differential diagnosis of sleep disorders in epilepsy treatment were highlighted, requiring a multidisciplinary approach due to the difficulty in distinguishing between symptoms caused by both epileptic activity and AEDs side effects as well as associated psychiatric disorders. To address these issues, an algorithm for diagnosis and correction of sleep disorders in epilepsy patients was proposed, aimed at optimizing therapy and improving the quality of life in this patient cohort.Conclusion. Sleep disorders in patients with epilepsy can lead to the formation of a “vicious circle” and worsen the course of both diseases, therefore, it is necessary to ensure their timely diagnosis and correction.